Avaliação da iluminação natural em habitação multifamiliar – conjunto habitacional Jardim Ipês - Rohr, Franciele (2019)
The creation of the Minha Casa Minha Vida Program (MCMV) by the Brazilian government has boosted the construction of social housing projects to reduce the large housing shortage in Brazil. Ten years after the launch of MCMV, the quality of these buildings has been questioned. Daylighting, focus of this research, is one of the issues that must be considered to achieve a better quality in these houses, because it interferes in the user´s comfort and health, as well as improves the building energy efficiency. This research aimed to evaluate the availability of natural lighting in housing units (UHs) of the Conjunto Habitacional Jardim Ipês (CHJI) that is part of the MCMV Program. The research is based on Post Occupancy Assessment (APO) focusing on users’ opinion about natural light conditions in their homes, as well as evaluating the annual estimation of daylight (EALN) through computer simulations with the APOLUX program. As a result, it was found that the majority of respondents' opinion about natural light (LN) in their UHs points to this as bright. Respondents were also asked about the activities performed in their UHs and it was found that require higher levels of illuminance than the minimum recommended by NBR 15575 (60 lux). The UHs reached RTQ-R requirements and local regulations regarding the minimum illumination levels. The NBR 15575 does not mention illuminances minimum values for housing and the local regulation does not indicate window areas for daylight. The simulation results showed that the UHs reached the parameters indicated in the RTQ-R simulation method and the minimum illuminances present in NBR 15575. In addition, all the UH reached the 120 lux criterion. However, the UHs do not reached the criterion of illuminance levels below 2,000 lux, although the rules do not give maximum illuminance indexes. The regulations should consider activities that require a higher level of illuminance in housing, as well as maximum levels considering users' reports about the need to use blackout curtains to avoid direct solar radiation and ensure privacy. As a main conclusion, it is proposed, for the rules and regulations, a requirement related to the maximum illuminance level allowed in residential environments as being 2,000 lux. Additionally a rule to recommended values of specific illuminance levels for houses that contemplate several activities that users can perform in residential environments, considering the research´s social and economic context.